The neuroscience of positive emotions and affect: Implications for cultivating happiness and wellbeing - Alexander, Rebecca; Aragón, Oriana R.; Bookwala, Jamila; Cherbuin, Nicolas; Gatt, Justine M.; Kahrilas, Ian J.; Kästner, Niklas; Lawrence, Alistair; Lowe, Leroy; Morrison, Robert G.; Mueller, Sven C.; Nusslock, Robin; et al. (Neuroscience and biobehavioral reviews, 2021)
•Neurophysiological correlates of positive emotions contribute to wellbeing.•Brain networks that implement positive emotions are flexible and modifiable.•Developmental, social, and environmental factors impact positive emotions.•Meditation, contemplative practices, and flow cultivate positive emotions.•Linguistic dimensions contribute to advancing the neuroscience of positive emotions. This review paper provides an integrative account regarding neurophysiological correlates of positive emotions and affect that cumulatively contribute to the scaffolding for happiness and wellbeing in humans and other animals. This paper reviews the associations among neurotransmitters, hormones, brain networks, and cognitive functions in the context of positive emotions and affect. Consideration of lifespan developmental perspectives are incorporated, and we also examine the impact of healthy social relationships and environmental contexts on the modulation of positive emotions and affect. The neurophysiological processes that implement positive emotions are dynamic and modifiable, and meditative practices as well as flow states that change patterns of brain function and ultimately support wellbeing are also discussed. This review is part of “The Human Affectome Project” (http://neuroqualia.org/background.php), and in order to advance a primary aim of the Human Affectome Project, we also reviewed relevant linguistic dimensions and terminology that characterizes positive emotions and wellbeing. These linguistic dimensions are discussed within the context of the neuroscience literature with the overarching goal of generating novel recommendations for advancing neuroscience research on positive emotions and wellbeing.